A Subjetividade Corporal Na Filosofia De Simone De Beauvoir - Nobrega, Mayara Catarina Bruni De [UNIFESP] (2018)
This Dissertation Argues That Simone De Beauvoir"S The Second Sex Offers A Singular Philosophy On The Embodiment Experience, Which May Be A Theoretical Alternative To "Sex" And "Gender" Distinctions In Some Feminist Critics. Beginning With The Hypothesis On Which The Philosopher Looks The Body Facticity Situation As A Relevant Aspect On The Existence Constitution Process, Without Falling In Biological Determinism, And Thinking On The Body, Not As A Knowledge Object, But As Lived Experience Of The Situated Liberation; We Consider The Possibility Of Reflecting On Bodies" Phenomenon Through Ambiguous And Situated Subjectivities, And Not Through An Essential Subject Concept. In This Way, We Are Searching For Phenomenological Descriptions On The Embodiment Experience In Which There Are Not Assumed As Anatomical Or Physiological Things, But Acknowledging The Body As The Realization Of Historical Meanings On Human Lives. Besides, This Also Means That The Body Experience Is Similar For Nobody Because The Becoming Is